Molecular mechanisms of drug resistance in renal cancer - Cieślak, Agata; Szenajch, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2005)
Renal cell carcinoma is highly resistant to systemic chemotherapy – the objective response rates do not exceed several percent for as well single agents as combine regimens. The existence of multifactorial multidrug resistance in this carcinoma is the reason of this state. Many cytostatics are chased away from renal cancer cells by the efflux pumps – MDR and MRP transporters. They are plasma membrane proteins, using energy from ATP hydrolysis to remove outside the cells such drugs like Vinca alkaloids, actinomycin-D, taxanes and cisplatin. Detoxification processes, using cytochrome P40s and glutathione, are strongly involved in resistance to ifosphamide, paclitaxel and cisplatin, carboplatin, doxorubicin, respectively. The levels of topoisomerase IIα – the enzyme involved in controlling the topologic states of DNA – are decreased in renal cell carcinoma lines with acquired resistance to etoposide. The relationship between drug resistance and expression of some oncogenes, like erbB-1, erbB-2, c-fos and Bcl-2 was also found. Mechanisms of multidrug resistance, involving both MDR and MRP transporters and glutathione, are very often the intrinsic ability of neoplastic cells, due to their existence in normal cells. Especially, this situation takes place in carcinomas of organs with excretory function. Renal cancer is considered to develop from proximal tubular epithelial cells, in which xenobiotics exporting pathways work very effectively. After tumor originating these mechanisms became the natural base of multidrug resistance developing. These circumstances seem to be the main reason of high resistance of renal cancer to a broad drug spectrum, commonly used in contemporary therapy.